2007
DOI: 10.1021/nn700184k
|View full text |Cite
|
Sign up to set email alerts
|

Imogolite Nanotubes: Stability, Electronic, and Mechanical Properties

Abstract: The aluminosilicate mineral imogolite is composed of single-walled nanotubes with stoichiometry of (HO)(3)Al(2)O(3)SiOH and occurs naturally in soils of volcanic origin. In the present work we study the stability and the electronic and mechanical properties of zigzag and armchair imogolite nanotubes using the density-functional tight-binding method. The (12,0) imogolite tube has the highest stability of all tubes studied here. Uniquely for nanotubes, imogolite has a minimum in the strain energy for the optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
247
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 189 publications
(275 citation statements)
references
References 40 publications
26
247
1
1
Order By: Relevance
“…Further research on these aluminogermanates indicates that this type of nanotube formation processes are faster and their packing is monoclinic and hexagonal as imogolite 30 . Its applications have focused on the possibility of developing biodevices able to detect biomolecules such as DNA, functioning as nanowires 53,57 .…”
Section: Imogolite and Its Potential In Nanotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…Further research on these aluminogermanates indicates that this type of nanotube formation processes are faster and their packing is monoclinic and hexagonal as imogolite 30 . Its applications have focused on the possibility of developing biodevices able to detect biomolecules such as DNA, functioning as nanowires 53,57 .…”
Section: Imogolite and Its Potential In Nanotechnologymentioning
confidence: 99%
“…Different theoretical studies estimated that the band gap of these aluminosilicates can vary between 3.67 to 10ev, depending on the calculation method used, which suggests that imogolite has insulating properties as semiconductor 7,53,57 . In a recent research Kuc and Heine (2009) raised the idea of a coaxial nanowire carbon nanotube (CNT) coated with an insulating sheath made of imogolite, which would broaden the scope of this nanomaterial to be used in nanoelectronic devices (see Figure 8) 54 .…”
Section: Imogolite and Its Potential In Nanotechnologymentioning
confidence: 99%
“…Several theoretical studies (Tamura & Kawamura, 2002;Konduri et al, 2006;Alvarez-Ramirez, 2007;Guimaraes et al, 2007;Zhao et al, 2009;Demichelis et al, 2010;Lee et al, 2011) using different methodologies indicated that there is clearly a minimum in the strain energy curve of the imogolite. However, the minimum value is still a matter of controversy.…”
Section: Imogolite Nanotubes -Stability and Structural Propertiesmentioning
confidence: 99%
“…The tube walls consist of a curved gibbsite-like sheet (Al(OH) 3 ), where the inner hydroxyl surface of the gibbsite is substituted by (SiO 3 )OH groups. This structure possesses a composition of (HO) 3 Al 2 O 3 SiOH, which is the sequence of atoms encountered on passing from the outer to the inner surface of the tube (Guimaraes et al, 2007). Halloysite is a clay mineral with stoichiometry Al 2 Si 2 O 5 (OH) 4 .nH 2 O that can grow into long tubules and is chemically similar to kaolinite (Giese & Datta, 1973;White et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation